Optical Detection of Inhibitor in Transformer Oil at Silicon-Detectable Wavelength Using Variable Path Length Model - Thiviyanathan V.A.; Ker P.J.; Leong Y.S.; Jamaludin M.Z.B.; Hannan M.A.; Mun L.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Chemical detection; Fourier transform infrared spectroscopy; Light sources; Optical correlation; Silicon; Conventional methods; Fundamental research; Mid-infrared regions; Optical path lengths; Oscillation models; Silicon Technologies; Strong correlation; Technical challenges; Oil filled transformers